Condition of Coral Fish on Maitara Island, Kota Tidore Kepulauan - Titaheluw, Syahnul Sardi; Naim, Armain; Bafagih, Aisyah; Andriani, Rovina (Sangia Research Media and Publishing, 2020)
Maitara Island has enormous natural resource potential to be developed as a tourist destination. One of the very potential is the Coral Reef ecosystem. This study aims to see the condition of reef fish on Maitara Island based on the Ecological Index. The study was carried out in June - July 2020. Data collection for reef fish using the Visual Method Census method included three (3) roles of fish, namely the role of major fish, indicators and targets. Data analysis in the form of Abundance, Diversity and Dominance. The results showed that the three roles of fish with a total of 86 species from 9 families. Major fish as many as 51 species consisting of families Pomacentridae (9 species), Caesoinidae (1 species), scaridae (2 species) and Labridae (7 species). The role of indicator fish is 15 species with 1 family (Chaetodontidae), and the role of target fish is 20 species consisting of 4 families (Serranidae, Siganudae, Latjunidae and Acanhuridae). The ecological index (Abundant, Diversity and Dominance) of reef fish at the study site is very low, which indicates high pressure on coral reefs and causes loss of ecological function and resilience. Utilization of coral reefs that do not pay attention to sustainability, such as taking coral reefs, haphazardly anchoring ships and bombing carried out decades ago directly impacted reef fish at the research site, where the abundance of fish at the observation station was at a value of 0.03 ind/ m2 and the diversity index does not exceed 0.5 ind/m2. The damage to the coral reefs of Maitara Island is mostly caused by anthropogenic activities, so that rehabilitation efforts must be carried out immediately to restore the condition of reef fish and protect the existence of Maitara Island from the threat of abrasion.